The mining for development framework for the Philippines - Cielo Magno (University of the Philippines, School of Economics (UPSE), 2015)
Mineral extraction alone is not sufficient to trigger sustainable development in developing countries. The mainstream paradigm on mining for development suggests that mineral-rich developing countries need to formulate a fiscal policy that can balance the need to maximize fiscal revenue while ensuring that the country has an attractive investment climate. The presence of mining companies in poor remote communities is sufficient to initiate development. In this discussion, it is suggested that the fiscal policy should take into account the state of governance where mining is being conducted, the extent of linkages mining creates in the local economy and whether the Regalian doctrine applies to ownership of minerals. The raise-to-the-bottom approach in designing fiscal policies does not necessarily benefit mineral-rich developing countries. In the case of the Philippines, a more comprehensive development framework is necessary to ensure that mining contribute to the sustainable development of the Philippines. The framework should include: (1) good governance of the public and extractive sectors which entails institutionalization of transparency and accountability mechanisms, implementation of the United Nations guiding principles on business and human rights and strengthening of government's regulatory capacity; (2) effective allocative capacity and capacity to effectively manage the returns from the sector by the government so that the proceeds from mining contribute to sustainable development and ensure intergenerational equity; (3) establishment of linkages between the extractive sector and the rest of the economy to maximize the benefit of the extractive activity; and (4) fiscal policy that reflects fair share in the extraction of resources, the state of mining governance and the environment where extraction is conducted. Fair share in mining includes payment for the minerals owned by the government on top of the regular taxes the government imposes to all industries.
Keywords: E62; L72; O13; H23; 330; mining; natural resource extraction; extractive industry; sustainable development; taxation